Reproductive toxicity and histopathological effects of heavy metal exposure in male Nile tilapia from the Brantas River, Indonesia - HABIB SYAIFUL ARIF TUSKA; ANIK MARTINAH HARIATI; ANWAR SANUSI; GATOT CIPTADI; BARLAH RUMHAYATI; HENDRA SUSANTO; GRETANIA RESIDIWATI; AULANNI’AM AULANNI’AM (Society for Indonesian Biodiversity, 2025)
Abstract. Tuska HSA, Hariati AM, Sanusi A, Ciptadi G, Rumhayati B, Susanto H, Residiwati G, Aulanni’am A. 2025. Reproductive toxicity and histopathological effects of heavy metal exposure in male Nile tilapia from the Brantas River, Indonesia. Biodiversitas 26: 5169-5180. Heavy metal pollution in freshwater ecosystems poses critical threats to fish health, particularly reproductive function. The Brantas River, one of Indonesia’s most economically important watersheds, has experienced escalating contamination due to industrial, agricultural, and domestic waste discharges, leading to ecological concern. This study aimed to evaluate the bioaccumulation and toxicological effects of heavy metals on histopathological alterations (necrosis, inflammation, hyperemia, and hyperplasia) in gills and testes, and on sperm quality (viability, DNA integrity, and morphological abnormalities) of male Nile tilapia (Oreochromis niloticus) from the Brantas River Basin, Malang, East Java, Indonesia. Water and tissue samples were collected from five river sites (25 male fish; 5 fish per site). Heavy metal levels in water were analyzed using Atomic Absorption Spectrophotometry (AAS). Histopathological scores were evaluated semi-quantitatively. Sperm viability, DNA fragmentation, and morphology were assessed microscopically. Statistical analyses included One-Way ANOVA and Spearman correlation tests (IBM SPSS 23.0; p<0.05). Cadmium (Cd) and iron (Fe) were found at elevated concentrations, particularly at Kalisari (Cd = 0.0129 ppm; Fe = 7.690 ppm]), exceeding WHO (0.003 and 0.3 ppm) and USEPA (0.005 and 0.3 ppm) guidelines. Fish from this site exhibited the most severe histopathological alterations in both gills and testes: necrosis (1.8±0.24; 2.27±0.70), inflammation (2.13±0.27; 2.00±0.85), hyperemia (1.93±0.27; 2.60±0.63), and hyperplasia (2.07±0.27; 2.33±0.72), respectively. Sperm quality was significantly compromised: viability (60.27±1.17%), DNA fragmentation (59.4±0.87%), and morphological abnormalities (43±1.47%) (p<0.05). Strong positive correlations were found between Fe levels and testicular inflammation (r?=?0.909), testicular hyperplasia (r?=?0.921), and gill hyperplasia (r?=?0.913) (p<0.05). Cd was negatively correlated with sperm plasma membrane integrity (r?=?-0.927) and DNA integrity (r?=?-0.896) (p<0.05). In conclusion, chronic exposure to Cd and Fe in the Brantas River is associated with marked tissue pathology and reduced reproductive performance in Nile tilapia. These findings underscore the urgent need for integrated river health monitoring and pollution control strategies to protect aquatic biodiversity and sustain ecosystem services in the Brantas River Basin.